2021
DOI: 10.1016/s1470-2045(21)00007-3
|View full text |Cite
|
Sign up to set email alerts
|

70-gene signature as an aid for treatment decisions in early breast cancer: updated results of the phase 3 randomised MINDACT trial with an exploratory analysis by age

Abstract: Background The MINDACT trial showed excellent 5-year distant metastasis-free survival of 94•7% (95% CI 92•5-96•2) in patients with breast cancer of high clinical and low genomic risk who did not receive chemotherapy. We present long-term follow-up results together with an exploratory analysis by age.Methods MINDACT was a multicentre, randomised, phase 3 trial done in 112 academic and community hospitals in nine European countries. Patients aged 18-70 years, with histologically confirmed primary invasive breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
195
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 227 publications
(245 citation statements)
references
References 19 publications
(41 reference statements)
4
195
0
13
Order By: Relevance
“…Hence, the benefit from adjuvant chemotherapy in premenopausal women was reproduced in RxPONDER. Similar results were also observed in an exploratory analysis of the MINDACT trial were an absolute chemotherapy benefit in distant metastasisfree survival (DMFS) of 5.0% was seen after 8 years of follow-up in patients ≤ 50 years with high clinical risk but low genomic risk according to MammaPrint [8]. In all of these three trials the rate of patients receiving OFS was low (between 3 and 16% in the different treatment arms) it is possible that this age dependent effect is a result of chemotherapy-induced OFS rather than of direct cytotoxicity.…”
Section: Rxponder Trial: Oncotype DX In Patients With 1-3 Positive Lymph Nodes [11]supporting
confidence: 72%
“…Hence, the benefit from adjuvant chemotherapy in premenopausal women was reproduced in RxPONDER. Similar results were also observed in an exploratory analysis of the MINDACT trial were an absolute chemotherapy benefit in distant metastasisfree survival (DMFS) of 5.0% was seen after 8 years of follow-up in patients ≤ 50 years with high clinical risk but low genomic risk according to MammaPrint [8]. In all of these three trials the rate of patients receiving OFS was low (between 3 and 16% in the different treatment arms) it is possible that this age dependent effect is a result of chemotherapy-induced OFS rather than of direct cytotoxicity.…”
Section: Rxponder Trial: Oncotype DX In Patients With 1-3 Positive Lymph Nodes [11]supporting
confidence: 72%
“…There are ongoing efforts to improve our diagnostic tools to identify ultralow risk tumors (those with minimal if any risk for metastasis) at the time of diagnosis, to reduce overtreatment [25]. In the treatment of breast cancer, we are increasingly targeting therapy with the intent to provide more effective treatment for those at highest risk of recurrence, and to de-escalate therapy in those with lowest risk [26,27]. These changes are occurring in every discipline involved with breast cancer treatment.…”
Section: The Debatementioning
confidence: 99%
“…However, the benefit of adjuvant chemotherapy seems to be age dependent: an underpowered exploratory analysis showed that c-riskehigh/griskelow patients aged <50 years might gain more benefit from adjuvant chemotherapy. 19,20 Of note, this prospective clinical trial provided strong evidence for the prognostic value of the MammaPrint test, but was not statistically powered to support its predictive value.…”
Section: Mammaprint and Blueprintmentioning
confidence: 92%